Environmentally safe decontamination and electrotechnology improvement sowing qualities of seed crops - Bereka, O.; Usenko, S. (Енергетика і автоматика, 2015)
Presented environmentally sound way to improve sanitation and sowing qualities crop seeds and hardware implementation.